Effects of Lagenaria Sicessaria Fruit Juice on Lipid Profile and Glycoprotein Contents in Cardiotoxicity Induced by Isoproterenol in Rats - Upaganlawar, Aman (Medknow Publications & Media Pvt Ltd, 2012)
This study investigated antihyperlipidemic effects of Lagenaria siceraria fruit juice (LSFJ) in isoproterenol (ISO)induced cardiotoxicity in rats. Rats treated with ISO (200 mg/kg, s.c.) showed a significant increase in the levels of triglycerides, cholesterol, and free fatty acids, in both serum and heart tissue. An increase in the levels of phospholipids, low-density lipoprotein, and very low-density lipoprotein-cholesterol, and decrease in high-density lipoprotein-cholesterol in serum and phospholipid levels in the heart were observed. ISO intoxicated rats also showed a significant decrease in the activities of lecithin: cholesterol acyl transferase, whereas lipoprotein lipase was found to be increased. Administration of LSFJ (400 mg/kg, p.o.) for 30 consecutive days and challenged with ISO on day 29th and 30th significantly attenuated these alterations and restored the levels of serum and heart lipids along with lipid metabolizing enzymes. Histopathological observations were also in correlation with the biochemical parameters. These findings indicate the protective effect of LSFJ during ISO-induced cardiotoxicity in rats.